PENGARUH STRATEGI PEMBELAJARAN AKTIF TERHADAP HASIL BELAJAR MATA PELAJARAN MENGGAMBAR TEKNIK 1 PADA SMKN 1 JAKARTA JURUSAN DESAIN PEMODELAN DAN INFORMASI BANGUNAN - Ammar Azmi (ADISAM PUBLISHER, 2026)
From now on, active learning techniques are being used. The teacher's role during the learning process is typically described as providing explanations of the subject matter and engaging in passive student listening. This page discusses active learning, particularly at vocational high schools, and attempts to give as many instances and an overview of applied learning in the classroom as it can. Descriptive analysis is the technique employed. In conclusion, Indonesian schools will adopt new active learning practices that will make even the most reticent pupils participate and fully value the learning process. Active learning, attentive instruction, and careful planning will improve the quality of learning by drawing students' attention to the learning process and giving them the chance to ask questions, have discussions, and make good use of the newly acquired knowledge while being approachable. The fact that this form of learning management exists could have an effect at the studying outcomes that students achieve.